Coronary Computed Tomography Angiography Assessment of High-Risk Plaques in Predicting Acute Coronary Syndrome - Lu, Guanyu; Ye, Weitao; Ou, Jiehao; Li, Xinyun; Tan, Zekun; Li, Tingyu; Liu, Hui (Frontiers in Cardiovascular Medicine, 2021)
Coronary computed tomography angiography (CCTA) is a comprehensive, noninvasive and cost-effective imaging assessment approach, which can provide the ability to identify the characteristics and morphology of high-risk atherosclerotic plaques associated with acute coronary syndrome (ACS). The development of CCTA and latest advances in emerging technologies, such as computational fluid dynamics (CFD), have made it possible not only to identify the morphological characteristics of high-risk plaques non-invasively, but also to assess the hemodynamic parameters, the environment surrounding coronaries and so on, which may help to predict the risk of ACS. In this review, we present how CCTA was used to characterize the composition and morphology of high-risk plaques prone to ACS and the current role of CCTA, including emerging CCTA technologies, advanced analysis and characterization techniques in prognosticating the occurrence of ACS.